Assessment of knowledge and awareness regarding intellectual property rights among the health-care professionals in Belagavi city: A cross-sectional study - Apurva Prashant Deshpande; Anil V Ankola; Roopali Sankeshwari; Sagar Jalihal; Laxmi Kabra; Deepika V Bhat; Abhra Roy Choudhury (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Intellectual property rights (IPRs) are increasingly becoming significant for sustainable growth of today's knowledge-based society. An inappropriate knowledge regarding IPR can fail to reserve rights for one's intellectual creation. Hence this study was planned with an aim to assess knowledge, awareness, and practices regarding intellectual property rights in India amongst the health-care professionals in Belagavi city. MATERIALS AND METHODS: A descriptive cross-sectional study was conducted among the postgraduate students and faculty of six health-care professional institutions in Belagavi, Karnataka. A total of 724 responses were recorded using convenient sampling. Data was collected using self-administered validated questionnaire which included demographic details and total 20 questions pertaining to knowledge, awareness, and practices regarding IPR. Two-point Likert scale was used. Descriptive statistics, Mann-Whitney U-test, and Chi-square test were applied. RESULTS: A total of 724 responses were recorded, 411 from postgraduate students and 313 from faculty of 6 health-care professional institutions. It was observed that 24.3% and 39.3% of postgraduate students and faculty participants, respectively, had maximum knowledge while 35.5% of faculty and 27.5% of postgraduate students had maximum awareness regarding IPR in India. Only 17.6% and 10.2% of faculty and postgraduate students had previously attended workshops on IPR. CONCLUSION: The present study identified that both faculty and postgraduate students of health-care profession have less knowledge and awareness regarding IPR. However, both knowledge and awareness regarding IPR were better among faculty when compared to postgraduate students. Thus, the academic community requires a higher level of sensitization and exposure to IPR in India.